2001
DOI: 10.1073/pnas.98.2.513
|View full text |Cite
|
Sign up to set email alerts
|

Cells adapted to the proteasome inhibitor 4-hydroxy- 5-iodo-3-nitrophenylacetyl-Leu-Leu-leucinal-vinyl sulfone require enzymatically active proteasomes for continued survival

Abstract: The proteasome is the primary protease used by cells for degrading proteins and generating peptide ligands for class I molecules of the major histocompatibility complex. Based on the properties of cells adapted to grow in the presence of the proteasome inhibitor 4-hydroxy-5-iodo-3-nitrophenylacetyl-Leu-Leu-leucinal-vinyl sulfone (NLVS), it was proposed that proteasomes can be replaced by alternative proteolytic systems, particularly a large proteolytic complex with a tripeptidyl peptidase II activity. Here we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
48
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 22 publications
2
48
0
Order By: Relevance
“…Proteolytic activity was monitored by the increased fluorescence resulting from the release of the AMC group (excitation/emission 380/440 nm). A total of 4 nmol peptide RU1 [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] was incubated with 12 l fractions 29, 31, and 32, respectively, for 20 min at 37°C. The digestion was stopped with 2% TFA and analyzed by MS as above.…”
Section: Protein Purificationmentioning
confidence: 99%
See 4 more Smart Citations
“…Proteolytic activity was monitored by the increased fluorescence resulting from the release of the AMC group (excitation/emission 380/440 nm). A total of 4 nmol peptide RU1 [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] was incubated with 12 l fractions 29, 31, and 32, respectively, for 20 min at 37°C. The digestion was stopped with 2% TFA and analyzed by MS as above.…”
Section: Protein Purificationmentioning
confidence: 99%
“…Earlier work, using the precursor peptide RU1 24 -47 , demonstrated that the exact C terminus of the antigenic peptide was directly produced by purified standard proteasome, but that the N terminus always carried additional 3 (RU1 [31][32][33][34][35][36][37][38][39][40][41][42] ) and 5 (RU1 29 -42 ) aa (16) (data not shown). This suggested that other peptidases might be necessary to trim the N-terminal extensions to the final nonamer RU1 34 -42 .…”
Section: Tpp II Mediates the Initial Trimming Of Ru1 29 -47 Precursormentioning
confidence: 99%
See 3 more Smart Citations